2019
DOI: 10.7554/elife.45952
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of fitness effects among synonymous mutations in a gene under directional selection

Abstract: The fitness effects of synonymous mutations, nucleotide changes that do not alter the encoded amino acid, have often been assumed to be neutral, but a growing body of evidence suggests otherwise. We used site-directed mutagenesis coupled with direct measures of competitive fitness to estimate the distribution of fitness effects among synonymous mutations for a gene under directional selection and capable of adapting via synonymous nucleotide changes. Synonymous mutations had highly variable fitness effects, bo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
86
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(94 citation statements)
references
References 44 publications
8
86
0
Order By: Relevance
“…Only 11 of these 89 outlier SNPs matched P. monodon transcriptome contigs [ 72 ] with subsequent protein translation of eight outlier SNPs demonstrating more non-synonymous changes than synonymous changes across all six reading frames. Despite the greater likelihood that non-synonymous mutations will have functional implications [ 73 , 74 ], all 11 of these outlier SNPs with P. monodon transcriptome matches should be considered as candidates for future research into divergent selection driven local adaptation among these geographically discrete populations [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Only 11 of these 89 outlier SNPs matched P. monodon transcriptome contigs [ 72 ] with subsequent protein translation of eight outlier SNPs demonstrating more non-synonymous changes than synonymous changes across all six reading frames. Despite the greater likelihood that non-synonymous mutations will have functional implications [ 73 , 74 ], all 11 of these outlier SNPs with P. monodon transcriptome matches should be considered as candidates for future research into divergent selection driven local adaptation among these geographically discrete populations [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, more recent studies have revealed that synonymous changes have an underestimated effect on fitness through their perturbances before and during translation. Synonymous sequence variance can impact fitness by changing the stability of mRNA (Kudla et al 2009;Kristofich et al 2018;Lebeuf-Taylor et al 2019) and altering codons to perturb or better match the codonanticodon ratio (Frumkin et al 2018). To our knowledge, we have shown here for the first time that synonymous sequence can also be essential for realising extreme parallel evolution.…”
Section: Discussionmentioning
confidence: 84%
“…Although this finding contradicts the intuition that so-called silent mutations should not imbue significant downstream impacts, it is less surprising in light of prior work demonstrating that these mutations can indeed enact non-trivial effects on splicing, transcript folding/stability, translational rates, co-translational folding/stability, and degradation 53,54 . Although NF1 splice mutations are often mistaken for silent mutations by sequencing methods 55,56 , evidence that synonymous mutations of the NF1 gene are selected in cancers such as T-cell acute lymphoblastic leukemia 57 signals a need for more research in this area.…”
Section: Subgroupings Outperform Mutation Subsets Chosen Using Varianmentioning
confidence: 99%